PENGARUH PENGGUNAAN GADGET TERHADAP HASIL BELAJAR ANAK USIA SD - Rara Aulia Fitri; Anggun Pasesa Nst; Elfia Sukma; Inggria Kharisma (STKIP Subang, 2026)
Rapid technological advancements have given rise to a variety of modern electronic devices known as gadgets. Initially, these devices were primarily used by adults as communication tools and sources of information. However, over time, gadget use has expanded beyond adults to include children, including elementary school children (SD), aged 6 to 12. This phenomenon has a two-way impact. On the one hand, gadgets provide easy access to various information sources and can be used as interactive learning media. On the other hand, uncontrolled gadget use has the potential to reduce children's concentration, diminish their interest in learning, and even lead to a decline in academic achievement. Therefore, parental involvement in supervising and guiding children in their gadget use is crucial and cannot be ignored.